Analysis of Determinant Factors of Operational Efficiency of Mass Transportation Modes and Their Implications for Social Welfare (Case Study of Urban Transport Networks) - Dwi Winahyo Sutrisna (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
The operational efficiency of mass transportation is a critical factor in urban mobility, with significant implications for social welfare. However, many cities in developing countries face challenges in achieving optimal efficiency, impacting service quality and community accessibility. This study aims to analyze the determinant factors of operational efficiency in urban mass transportation modes and examine their implications for social welfare in the context of Indonesian cities. Employing a quantitative approach, this research utilized Data Envelopment Analysis (DEA) and multiple regression methods to evaluate 15 urban transportation corridors across Jakarta, Surabaya, and Bandung during the 2022-2024 period. Data were collected through direct observation, surveys of 1,200 passengers, and in-depth interviews with operators and regulators. The analysis revealed that service frequency, load factor ratio, and fleet quality are the dominant factors affecting operational efficiency, collectively contributing 68.4% to efficiency variations. Operational efficiency demonstrated a strong positive correlation with accessibility for low-income populations (r=0.742) and contributed to reducing household transportation costs by up to 23.6%. Furthermore, efficient corridors showed significantly lower carbon emissions (0.68 kg CO? per passenger-km) compared to inefficient corridors. The findings underscore the crucial relationship between transportation operational efficiency and social welfare outcomes. To maximize both efficiency and social benefits, policymakers should prioritize fleet modernization, optimize operational schedules, and enhance system integration through coordinated tariff structures and infrastructure development.